Ultrasound-Guided Modified Seldinger Placement of Tenckhoff Catheters in Pediatric Patients Undergoing Peritoneal Dialysis: Single Center Experience - Yu, Yang; Xie, Qing; Chen, Yaxian; Hu, Wanmei; Zhang, Panpan; Huang, Shi; Yang, Fengjie; He, Yonghua; Yi, Yonghong; Zhou, Jianhua; Zhang, Yu (Frontiers in Pediatrics, 2022)
Minimally invasive peritoneal dialysis (PD) catheterization is increasingly common, and percutaneous PD catheters may be placed using a trocar or the Seldinger technique. There are few reports of pediatric percutaneous PD catheter insertion. We retrospectively compared the outcomes from percutaneous placement of Tenckhoff catheters using a modified Seldinger technique with catheter placement by open surgery. This single-center retrospective study compared 14 pediatric patients who received percutaneous PD catheter insertion using an ultrasound-guided modified Seldinger technique (August 2018 to February 2021) with 10 patients who received open-surgical PD catheter insertion (2015-2018). Complications and catheter survival were evaluated. The overall technical success rate was 100%, but the Seldinger technique required less time (30 vs 45 min) and smaller incisions (1.1 vs 4.4 cm). The early complications in the Seldinger and control groups were bleeding (1 vs 0), catheter dysfunction (1 vs 1), abdominal pain (3 vs 7), and exit leakage (0 vs 1). In the Seldinger group, the median time from insertion to first use was 3 days, and the minimum follow-up was 6 months. Catheter survival at 6 months was 93% (Seldinger group) and 90% (open surgery group). The adoption of this technique at our institution led to a significant increase in the percentage of new pediatric dialysis patients commencing PD rather than hemodialysis. Collectively, the modified Seldinger technique described here was safe and feasible in pediatric patients. This approach is simpler and more rapid than open surgery, and reduces early complications and increases PD uptake.